2021
DOI: 10.3390/molecules26113406
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High Fat Diet on Cerebrovascular Health and Pathology: A Species Comparative Review

Abstract: In both humans and animal models, consumption of a high-saturated-fat diet has been linked to vascular dysfunction and cognitive impairments. Laboratory animals provide excellent models for more invasive high-fat-diet-related research. However, the physiological differences between humans and common animal models in terms of how they react metabolically to high-fat diets need to be considered. Here, we review the factors that may affect the translatability of mechanistic research in animal models, paying speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 177 publications
(254 reference statements)
0
10
0
Order By: Relevance
“…The authors later showed that a diet containing as little as 20% saturated fatty acid (SFA) content was enough to impair cognition in young rodents ( Greenwood and Winocur, 2005 ). Since those initial studies, a large body of work, including work from our group, has confirmed the finding that an HFD can impair cognition, in both rodents and humans ( Freeman et al, 2013 ; Johnson et al, 2016 ; Kalmijn, 2000 ; Miranda et al, 2018 ; Smith et al, 2011 ; Winocur and Greenwood, 2005 ; Zimmerman et al, 2021 ).…”
Section: Introductionmentioning
confidence: 69%
“…The authors later showed that a diet containing as little as 20% saturated fatty acid (SFA) content was enough to impair cognition in young rodents ( Greenwood and Winocur, 2005 ). Since those initial studies, a large body of work, including work from our group, has confirmed the finding that an HFD can impair cognition, in both rodents and humans ( Freeman et al, 2013 ; Johnson et al, 2016 ; Kalmijn, 2000 ; Miranda et al, 2018 ; Smith et al, 2011 ; Winocur and Greenwood, 2005 ; Zimmerman et al, 2021 ).…”
Section: Introductionmentioning
confidence: 69%
“…In contrast, in a eubiotic state, the BLB protects the cochlea from pathogens, which would otherwise compromise cochlear integrity, causing inflammation and injury. This can be postulated based on evidence that the BBB [189][190][191] and the BLB [192,193] increase their permeability in response to the increased presence of the bacterial metabolite LPS.…”
Section: Could There Be a Similar Connection To The Inner Ear?mentioning
confidence: 99%
“…However, not all postmenopausal women are susceptible to neurological disease ( Tamaria et al, 2013 ). A high-fat diet (HFD) is considered a risk factor for multiple diseases, such as gastrointestinal cancer ( Tong et al, 2021 ), cerebrovascular disease ( Zimmerman et al, 2021 ), and AD ( Barnes and Yaffe, 2011 ), as well as for postmenopausal women ( Naworska and Bak-Sosnowska, 2019 ). A previous study demonstrated that an HFD accelerated cognitive decline in estrogen-deficient rats by aggravating mitochondrial and synaptic dysfunction (Pratchayasakul et al, 2015).…”
Section: Introductionmentioning
confidence: 99%